In situ visualization of the superior nanomechanical flexibility of individual hydroxyapatite nanobelts. Issue 8 (7th February 2018) - Qi, Mei-li; Huang, Zhennan; Yao, Wentao; Long, Fei; Cheng, Meng; Song, Boao; Banner, David; Shahbazian-Yassar, Reza; Lu, Yu-peng; Shokuhfar, Tolou
Abstract : Under an external compression force, a multi-layered HA nanobelt can be deformed easily at an extreme angle, whereas, a traditional HA nanorod fractured suddenly with the generation of multiple cracks. Abstract : Highly flexible multi-layered hydroxyapatite (HA) nanobelts were successfully grown and compared to nanorods. The nanomechanical behaviour of individual HA nanostructures was visualized using in situ TEM. Compression-induced deformation in HA nanobelts can spontaneously recover at a maximal strain of 99.2%, much larger than the 2.63% failure strain observed for traditional HA nanorods.